Nanoscale cobalt doped carbon aerogel: microstructure and isosteric heat of hydrogen adsorption - Tian, Hu-Yong; Buckley, Craig; Paskevicius, Mark; Sheppard, Drew; Wang, Shaobin; Webb, C.; Gray, E. (Elsevier Ltd, 2011)
The incorporation of nanoscale Co particles (with sizes from a few nanometres) into porous carbon aerogels (CAs) was investigated. Elemental maps of the nanoscale metal particles embedded within CA were obtained using energy filtered transmission electron microscopy. The microstructure of Co doped carbon aerogels was further investigated using small angle X-ray scattering and nitrogen adsorption at 77 K. The isosteric heat of adsorption (Qst) was investigated as a function of hydrogen uptake at temperatures from 77 K to 110 K over the pressure range of 0–0.25 MPa. The isosteric heat of adsorption at low H2 concentration for Co doped CA (9.0 kJ mol−1) was found to be higher than for pure CA (5.8 kJ mol−1).